Scientific Creativity In More Than 60 Years: A Bibliometric Analysis - Berry Devanda; Lufri; Ali Amran; Yuni Ahda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Although research on student scientific creativity can be found easily on the literature, it is difficult to get articles on how scientific creativity is presented for some decades. This article report scientific creativity from 1960 to 2022 which mined from Scopus database. 181 articles were analyzed using a bibliometric analysis. Publish or Perish (PoP), Mendeley and Vos Viewer were used to find the map of literature on scientific creativity. Keyword used in this research was merely “Scientific Creativity”. The results of the analysis using Vos Viewer show some interesting findings. First, although there have been publications published since 1960 on scientific creativity, from 2008 to 2022 the number of studies on this topic increased significantly. This may be due to the increasing attention of researchers to 21st century skills, creativity and other skills. Second, several findings from Vos Viewer show that there is no collaboration among researchers on scientific creativity that should be able to improve the quality and productivity of research around the topic. Third, the topics about the model and the effectiveness of scientific creativity are increasing. This matter can be taken into consideration by researchers to be used as the next research.